A Systematic Review: Significance of Plyometric Training on Functional Performance and Bone Mineral Density in Basketball Players of Different Age Groups - A. T. Anversha; V. Ramalingam (Спортивная медицина: наука и практика)
Aim: Basketball necessitates a holistic approach to player development, encompassing both skill and physicality, with a critical emphasis on understanding these requirements due to its complex tactics. Plyometric training’s potential in sport performance lacks comprehensive research. This systematic review, guided by PRISMA guidelines, aims to analyse diverse range of literature concerning healthy athletes, investigating its significance on functional performance and bone mineral density in basketball players of different age groups (pre-teen, adolescent, and young adult).Methods: The study conducted electronic searches in databases like PubMed, ScienceDirect, and ResearchGate, supplemented with manual reference searches, covering the period from 2013 to June 2023. Initially, 783 items were identified. Inclusion criteria involved English-language publications focusing on basketball players aged 8 to 28 years, assessing plyometric training’s effect on functional performance with quantitative measurements. Screening began with titles and abstracts, followed by full-text evaluation to ensure eligibility.Results: A database search yielded 26 peer-reviewed articles, primarily randomized controlled trials, showing significant functional improvements through plyometric training (4-36 weeks, 2-3 times weekly). Assessments covered explosive leg power, agility, sprinting, muscle strength, and bone density. Male participants dominated, but female and mixed-gender groups were included. Results consistently highlighted plyometric training’s positive impact with statistical significance.Conclusion: This review provides evidence that plyometric training improves agility, sprinting ability, leg power, basketball skills as well as BMD across different age groups of players. It establishes plyometrics as effective for boosting on-court performance. Integrating plyometric training holds great promise in advancing athlete success in basketball.